The Impact of Internal Communication on Employee Satisfaction at a Workplace - Bolfek, Berislav; Milković, Viktorija; Lukovac, Marko (Oeconomica Jadertina, 2017)
Communication is the basic element of socialization of every individual and plays a key role in creating relationships with family, friends, associates and business partners. Therefore communication is a process that is present everyday in both the private as well as the business world. Communication is a process of understanding, transferring information, creating new knowledge and ideas, and is one of the basic preconditions without which you cannot succeed in doing business. Internal communication represents the process of exchange of information, ideas, thoughts and plans between people within the organization. Efficient internal communication contributes to establishing good relations in the organization and improving the overall status within the organization. Internal communication is one of the most important factors affecting employee satisfaction, reflecting on the productivity of employees and affecting the success of a business. This paper presents a research carried out in order to establish the level of job satisfaction and internal communication of the employees of a dealership and medical equipment distribution company.